To read or not to read: a neurophysiological study - Mares, I.; Custódio, P.; Fonseca, J.; Bentes, C.; Guerreiro, M.; Guimarães, N.; Martins, I. P. (Neurocase, 2015)
Pure alexia (PA) has been associated with visual deficits or a failure to activate the visual word form area (VWFA). We report a patient with pure alexia due to posterior cortical atrophy, in whom event-related potentials revealed a delay in the P100 component and an absent N170 compared with controls. Furthermore, there was a tendency for a larger delay in P100 latencies associated with incorrectly read words. This suggests that some cases of PA might result from deficits in visual perception, signaled by the P100 early potential which could lead to an inability to consistently activate the VWFA, marked by the absent N170.